Progress-based Regulation of Low-importance Processes - Douceur, John (JD); Bolosky, Bill (Operating Systems Review, 1999)
MS Manners is a mechanism that employs progress based regulation to prevent resource contention with low importance processes from degrading the performance of high importance processes. The mechanism assumes that resource contention that degrades the performance of a high importance process will also retard the progress of the low importance process. MS Manners detects this contention by monitoring the progress of the low importance process and inferring resource contention from a drop in the progress rate. This technique recognizes contention over any system resource, as long as the performance impact on contending processes is roughly symmetric. MS Manners employs statistical mechanisms to deal with stochastic progress measurements; it automatically calibrates a target progress rate, so no manual tuning is required; it supports multiple progress metrics from applications that perform several distinct tasks; and it orchestrates multiple low importance processes to prevent measurement interference. Experiments with two low importance applications show that MS Manners can reduce the degradation of high importance processes by up to an order of magnitude.